Elite Vs. Folk Bilingualism: The Mismatch between Theories and Educational and Social Conditions - Carmen Helena Guerrero (Asociación Colombiana de Profesores de Ingles, 2010)
This article aims at contributing to the ongoing discussion about how bilingualism is understood in the current National Bilingualism Plan (PNB for its initials in Spanish). Based on previous research and discussions held at academic events, it is evident that the promoters of the PNB use the term "bilingualism" in a rather indiscriminate way, without adopting a clear approach or definition. This ambiguity in conceptualization has serious consequences in the way the PNB is implemented around the country. The main contribution of this reflection article is, then, to explore from a theoretical perspective two opposite types of bilingualism: elite/folk bilingualism to show that even though on the surface the PNB seems to aim at an elite bilingualism, the educational and social conditions show otherwise.